Effects of foot-and-mouth disease on the Brazilian economy: a computable general equilibrium analysis - Menezes, Taís Cristina de (2022)
This thesis analyzes the economic impacts of hypothetical foot-and-mouth disease (FMD) outbreaks in Brazil. The first analysis deals with the impact of FMD outbreaks on welfare in Brazil and other countries and on beef and pork bilateral trade between different countries. The second analysis consists of evaluating the impact of FMD outbreaks in different Brazilian regions, including an assessment of changes in macroeconomic variables (such as gross domestic product, investment and exports), wages and employment. Two computable general equilibrium models are applied. In the first analysis, the GTAP model, which includes data for 141 countries and regions, is employed, while the second analysis applies the Brazilian interregional model TERM-BR. The results of both studies provide a basis for estimating the economic and social impacts of FMD outbreaks on the Brazilian economy and on Brazilian meat export markets. These studies show the importance of preventing animal diseases in Brazil for the maintenance of livestock production and exports. The results of this thesis can help the formulation of policies and strategies to minimize the socioeconomic losses from potential outbreaks of FMD in the country. Additionally, the methodology developed in this research can contribute to the formulation of strategies aimed at other animal diseases still present in Brazil.